2011
DOI: 10.4103/0256-4947.77491
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological spectrum of IgA nephropathy in Kuwait

Abstract: BACKGROUND:Little is known about the nature and the course of IgA nephropathy (IgAN) in Arab countries. The aim of this work was to study the spectrum of clinical presentation and histopathological findings at our institution.DESIGN AND SETTING:Retrospective review, all renal biopsies at the Mubarak Al Kabeer Hospital between January 2000 and December 2004.METHODS:Cases of IgA nephropathy were selected, and their medical records and biopsy findings were reviewed.RESULTS:Eighty patients (9.2% of all native kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Multivariable logistic regression showed that the presence of mild hematuria was a significant predictor (OR, 2.3; 95% CI, 1.2–4.3). A Kuwait study [ 38 ] with 69 IgAN patients suggested that deterioration of renal function during the follow-up period (mean follow-up duration, 3.5 years) was more significant in the presence of macroscopic hematuria at the time of biopsy ( p < .05). The crude RR was 1.47 (95% CI, 0.90–2.40).…”
Section: Resultsmentioning
confidence: 99%
“…Multivariable logistic regression showed that the presence of mild hematuria was a significant predictor (OR, 2.3; 95% CI, 1.2–4.3). A Kuwait study [ 38 ] with 69 IgAN patients suggested that deterioration of renal function during the follow-up period (mean follow-up duration, 3.5 years) was more significant in the presence of macroscopic hematuria at the time of biopsy ( p < .05). The crude RR was 1.47 (95% CI, 0.90–2.40).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of 5,660 IgAN patients from 13 literatures (He et al, 2021) concluded that initial microscopic hematuria and persistent hematuria may be associated with renal progression and ESRD. A Kuwaiti study of 69 IgAN patients (Ghani et al, 2011) showed that renal function deterioration was more significant during follow-up (mean followup 3.5 years) in the presence of gross hematuria at biopsy. Our center has been paying close attention to IgAN patients with hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore clear that the role of serum uric acid in IgAN is still controversial. Nonetheless, a large number of previous studies rarely included the analysis of pathological data and the baseline value of serum uric acid at renal biopsy was used as the research index (Ghani et al 2011;Le et al 2012;Liu et al 2018;Matsukuma et al 2017;Moriyama et al 2015;Nagasawa et al 2016). However, the baseline value of serum uric acid may not accurately re ect the dynamic level of serum uric acid during the follow-up period because the level of blood uric acid uctuates greatly and is easily affected by speci c food and eating habits (Roddy et al 2018).…”
Section: Introductionmentioning
confidence: 99%